New Laminated Displacement-Discontinuity Program: Fundamental Behavior - Keith A. Heasley (International Conference on Ground Control in Mining, 1996)
In the past, numerous displacement-discontinuity (DD) models of stratified rock masses have been proposed using a homogeneous isotropic elastic overburden. In this paper, it is postulated that a laminated overburden model might be more accurate for describing the displacements and stress in these stratified deposits. In order to investigate the utility of using a laminated overburden in a DD model, the fundamental mathematical basis of the laminated model is presented and graphically compared with the fundamental behavior of homogeneous isotropic elastic overburden and with field data. Specifically, the stresses and displacements surrounding an idealized longwall panel as determined from the laminated overburden model are presented and compared with results from the homogeneous isotropic overburden and with measured abutment stress data. Also, the remote displacements and surface subsidence as calculated by the laminated overburden model are compared with homogeneous isotropic calculations and with measured subsidence data. The results of this investigation show that the laminated overburden is more supple, apt to propagate displacements and stress further, and better able to fit observed data than the classic homogeneous isotropic overburden. Ultimately, it is suggested that the laminated model has the potential to increase the accuracy of displacement and stress calculations for a variety of mining situations.